THE NEW CIVIL CODE - IDENTIFICATION OF THE LEGAL PERSON - SILVIA-LUCIA CRISTEA; LUCIAN-FLORIN ONISOR (Challenges of the Knowledge Society)
The article presents issues related to the identification of the legal person in the New Civil Code and in the commercial law special regulations, namely the Law 26/1990 regarding the Commercial Register and the Law no 31/1990 regarding commercial companies. This study aims at identifying the areas where the commercial law, a law for the professionals in the field, has brought changes into the civil law as common law; therefore, this study is meant for academics and professionals in the field. One outcome of this study is the identification of new attributes such as: bank account, registration number for VAT purpose, telephone, fax, and equity, apart from the identification attributes included in the New Civil Code, such as: name, registered office and nationality, registration number and the unique registration number.